2020
DOI: 10.1021/acschemneuro.0c00067
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Differently Modulates Group I Metabotropic Glutamate Receptors Depending on Age in SAMP8 Mice

Abstract: Glutamate homeostasis is critical for neurotransmission as this excitatory neurotransmitter has a relevant role in cognition functions through ionotropic and metabotropic glutamate receptors in the central nervous system. During the last years, the role of the group I metabotropic glutamate receptors (mGluRs) in neurodegenerative diseases such as Alzheimer's disease has been intensely investigated. Resveratrol (RSV) is a natural polyphenolic compound that is thought to have neuroprotective properties for human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 80 publications
4
12
0
Order By: Relevance
“…An age-related reduction in glutamate levels in the whole brain of SAMP8 mice from five- to seven-month-old mice was previously reported by our group [ 64 ]. In the present work, covering a wider time frame (3, 6, and 12 months) and a limited region (cerebral cortex), glutamate levels in SAMR1 mice were similar at three and six months, but decreased at 12 months.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…An age-related reduction in glutamate levels in the whole brain of SAMP8 mice from five- to seven-month-old mice was previously reported by our group [ 64 ]. In the present work, covering a wider time frame (3, 6, and 12 months) and a limited region (cerebral cortex), glutamate levels in SAMR1 mice were similar at three and six months, but decreased at 12 months.…”
Section: Discussionsupporting
confidence: 59%
“…Adenosine signaling also interacts with many other neurotransmitter systems such as glutamatergic signaling [ 56 , 57 ], which is also modulated by aging and has a role in neurodegeneration [ 58 , 59 , 60 , 61 ]. The glutamatergic system has been found to be altered in the human brain in AD patients [ 62 , 63 ] and also in the whole brain of SAMP8 mice [ 64 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the whole-brain from SAMP8 mice, we have reported an age-related downregulation and desensitization of the A 1 receptor whereas A 2A was found to be fully functional [29,38]. Also mGluR 5 significantly decreased with aging [30]. These previous data suggest SAMP8 mice as a suitable model for ARs and mGluRs related research on neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 59%
“…However, an in vivo study by PET revealed a downregulation of mGluR 5 caused by Aβ in the limbic system in the 5xFAD mouse model as compared to wild type [60]. We have recently described a significant age-associated decrease in mGluR 5 density in the whole-brain of SAMP8 mice [30]. Interestingly, in the present work, a significant and robust reduction in mGluR 5 density was also detected in blood serum and exosomal fraction from 5 to 7-month-old.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation